0253 Hairdressers are occupationally exposed to ortho- and meta- toluidine0253 Hairdressers are occupationally exposed to ortho- and meta- toluidine. (23rd June 2014) - Albin, Maria; Johansson, Gabriella; Jönsson, Bo; Axmon, Anna; Lindh, Christian; Lind, Marie-Louise; Gustavsson, Mats; Broberg Palmgren, Karin; Boman, Anders; Meding, Birgitta; Lidén, Carola
Abstract : Objectives: Hairdressing work is classified as carcinogenic based on excess risk for bladder cancer. We aimed at evaluating if current hairdressers are exposed to established/suspected bladder carcinogens (aromatic amines) and indicate possible sources of exposure. Method: Hairdressing salons listed in the telephone book were contacted for personal visits, 295 hairdressers were recruited (an estimated half of the eligible invited subjects). For comparison we included 32 consumers and 60 controls employed at our hospital. The study was restricted to female non-smokers. Questionnaires including frequency of performed work tasks were filled in by the hairdressers, and all subjects reported personal hair dye use, and exposure to environmental tobacco smoke. Blood samples were taken for analysis (gas chromatography-tandem mass spectrometry; GC-MS/MS) of ortho (o)-, meta (m)-, and para (p)-toluidine; 2-, 3-, and 4-ethylaniline, 2, 3- and 3, 4-dimethylaniline as haemoglobin adducts. Results: Adduct concentrations did not differ significantly between hairdressers, consumers and controls. However, for hairdressers, o- and m-toluidine concentrations increased with the weekly performed number of permanent hair dyeings (p = 0.026), and hair waving treatments (p = 0.020). o- and m-Toluidine concentrations also tended (p = 0.076 and 0.080, respectively) to increase with the frequency of light colour permanent hair dyeings. The results were not driven by personal hair dye use, or smoking (key subjects additionally evaluated for cotinine). Analysis of a randomly chosen hair waving product confirmed the presence of o-and m-toluidine. Conclusions: Our observations indicate that hairdressers are currently exposed to an established (o-toluidine), and a suspected (m-toluidine), human carcinogen from permanent hair dyes (including light colours) and unexpectedly also from hair waving.